1997
DOI: 10.1007/bf02303795
|View full text |Cite
|
Sign up to set email alerts
|

Extended resection for locally advanced colorectal carcinoma

Abstract: There is no statistically significant difference in the 5-year survival rates when multiple ASOS are resected; therefore, an aggressive surgical approach is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 11 publications
4
25
1
3
Order By: Relevance
“…The incidence of neoplastic infiltration is similar to result reported by Eisenberg et al [8], but it is higher than rates reported by others [4,6,7,[12][13][14][15][16][17]. This difference may result from the fact that more advanced tumors were treated in our hospital.…”
Section: Journal Of Surgical Oncologysupporting
confidence: 89%
See 1 more Smart Citation
“…The incidence of neoplastic infiltration is similar to result reported by Eisenberg et al [8], but it is higher than rates reported by others [4,6,7,[12][13][14][15][16][17]. This difference may result from the fact that more advanced tumors were treated in our hospital.…”
Section: Journal Of Surgical Oncologysupporting
confidence: 89%
“…Reportedly, histologic tumor infiltration is demonstrated in 39-84% of cases in which the tumor is found to be adherent to the adjacent viscera whereas the rest represent inflammatory adherence [4,[6][7][8][12][13][14][15][16][17]. Any attempt to separate the carcinoma from adherent organs may lead to tearing or transection of the tumor with the risk of intraoperative dissemination of tumor cells, resulting in early local recurrence [1,4,6,15].…”
Section: Discussionmentioning
confidence: 99%
“…Curative ERs (B3 and C3) are safe, with survival rates similar to traditional resections (B2 = C2 = T3N0 and T3N1-2) 1,4 , the lymph node status being the major prognostic factor [2][3][4] . Multi-visceral resection is a decision made intraoperatively as adhesions to surrounding organs or structures may be only inflammatory [1][2][3][4] .…”
Section: Case Report Case Report Case Report Case Report Case Reportmentioning
confidence: 94%
“…Articles that discuss survival in colorectal extended resections (ER) typically use the Dukes staging modified by Gunderson-Sosin 1,2 : B3 (T4No) and C3 (T4N1-2). In the past, en bloc ER was suggested by Moynihan in 1926, and its applicability was statistically proven by Sugarbacker 2 in 1946 with 56% disease-free survival at five years.…”
Section: Case Report Case Report Case Report Case Report Case Reportmentioning
confidence: 99%
See 1 more Smart Citation